Proinflammatory and Immunoregulatory Roles of Eicosanoids in T Cells - Lone, Anna M.; Taskén, Kjetil (Frontiers in Immunology, 2013)
Eicosanoids are inflammatory mediators primarily generated by hydrolysis of membrane phospholipids by phospholipase A2 to ω-3 and ω-6 C-20 fatty acids that next are converted to leukotrienes (LTs), prostaglandins (PGs), prostacyclins (PCs) and thromboxanes (TXAs). The rate-limiting and tightly regulated lipoxygenases control synthesis of LTs while the equally well-controlled cyclooxygenases 1 and 2 generate prostanoids, including PGs, PCs and TXAs. While many of the classical signs of inflammation such as redness, swelling, pain and heat are caused by eicosanoid species with vasoactive, pyretic and pain-inducing effects locally, some eicosanoids also regulate T cell functions. Here, we will review eicosanoid production in T cell subsets and the inflammatory and immunoregulatory functions of LTs, PGs, PCs and TXAs in T cells.